PHYTOREMEDIATION USING EICHHORNIA CRASSIPES AQUATIC PLANT - Majid, A.; Siddique, N. (The Nucleus, 2013)
Phytoremediation is a cost effective approach for the treatment of polluted soil and contaminated water. The effectiveness of one aquatic plant Eichhornia crassipes was evaluated for its capability in removing copper from copper solution using atomic absorption spectroscopy (AAS). The aquatic plant was placed in solutions containing 2 mg/L, 4 mg/L and 6 mg/L of copper, for a period of 18 days and the change in Cu concentration was measured. Results showed an increase of copper within the plants’ root and shoot tissues and a decrease of copper concentration in the solution. It was found that roots tend to accumulate a higher amount of copper than shoots due to translocation process. The maximum growth of Eichhornia crassipes was in the 2 mg/L solution which shows that growth was affected by the presence of Cu in the water. The maximum removal of copper in the solutions containing Eichhornia crassipes was 87.5% from the 4 mg/L solution. Eichhornia crassipes accumulated upto 1265.0 mg/kg of Cu in its roots indicating that this aquatic plant species may be used as a hyper-accumulator for copper.